New Approaches to Translation, Conflict and Memory: Narratives of the Spanish Civil War and the Dictatorship. Edited by Lucía Pintado Gutiérrez and Alicia Castillo Villanueva. Cham: Palgrave Macmillan, 2019. 234 pp. Hb. ISBN: 978-3-030-00697-6. - Hijjo, Nael F M (Hikma, 2019)
New Approaches to Translation, Conflict and Memory: Narratives of the Spanish Civil War and the Dictatorship. Edited by Lucía Pintado Gutiérrez and Alicia Castillo Villanueva. Cham: Palgrave Macmillan, 2019. 234 pp. Hb. ISBN: 978-3-030-00697-6. $119.99.